2007
DOI: 10.3171/jns-07/11/0917
|View full text |Cite
|
Sign up to set email alerts
|

Hearing preservation following fractionated stereotactic radiotherapy for vestibular schwannomas: prognostic implications of cochlear dose

Abstract: The radiation dose to the cochlea is strongly predictive for subsequent hearing deterioration. It is essential for the cochlea to be outlined as an organ at risk, and for radiation techniques to be optimized, to improve long-term hearing preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 50 publications
0
45
1
1
Order By: Relevance
“…All studies that reported the details of their planning techniques used both computed tomography and MRI treatment plans (47,51,52,54,56,57,59,60). Most institutions used a 1-2-mm margin on the contrast-enhancing tumor as seen on MRI (52,54,56,57,59,60). Using various fractionation schemes, the rate of trigeminal and facial nerve preservation has been $95% and $94%, respectively (47,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Fractionated Stereotactic Rtmentioning
confidence: 97%
See 4 more Smart Citations
“…All studies that reported the details of their planning techniques used both computed tomography and MRI treatment plans (47,51,52,54,56,57,59,60). Most institutions used a 1-2-mm margin on the contrast-enhancing tumor as seen on MRI (52,54,56,57,59,60). Using various fractionation schemes, the rate of trigeminal and facial nerve preservation has been $95% and $94%, respectively (47,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Fractionated Stereotactic Rtmentioning
confidence: 97%
“…Most institutions used a 1-2-mm margin on the contrast-enhancing tumor as seen on MRI (52,54,56,57,59,60). Using various fractionation schemes, the rate of trigeminal and facial nerve preservation has been $95% and $94%, respectively (47,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Fractionated Stereotactic Rtmentioning
confidence: 97%
See 3 more Smart Citations